Fiscal forecasting: lessons from the literature and challenges - Teresa Leal; Javier J. Pérez; Mika Tujula; Jean-Pierre Vidal (European Central Bank (ECB), 2007)
While fiscal forecasting and monitoring has its roots in the accountability of governments for the use of public funds in democracies, the Stability and Growth Pact has significantly increased interest in budgetary forecasts in Europe, where they play a key role in the EU multilateral budgetary surveillance. In view of the increased prominence and sensitivity of budgetary forecasts, which may lead to them being influenced by strategic and political factors, this paper discusses the main issues and challenges in the field of fiscal forecasting from a practitioner's perspective and places them in the context of the related literature.
Keywords: H6; E62; C53; 330; Fiscal policies; forecasting; government budget; monitoring; Finanzpolitik; Öffentlicher Haushalt; Wirtschaftsprognose; Prognoseverfahren; Vergleich